PEMBELAJARAN KAYANG MELALUI PENDEKATAN BERMAIN â€œRAMBOâ€ PADA SISWA KELAS IV SEKOLAH DASAR NEGERI KAJAR KECAMATAN LASEM KABUPATEN REMBANG TAHUN PELAJARAN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
This classroom action research consisted of two cycles, each cycle includes: planning, action, observation andreflection. Prior to the study, the learning outcomes Kayang Elementary School fourth grade students Kajar asmany as 18 of t he 24 children (66%) did not pass KKM with an average value of 6.54. Based on the results ofthis study illustrated that the implementation of learning through play kayang wall propagation in fourthgrade elementary school students in the first cycle Kajar mastery learning as many as 15 students or 62.5% andthe average val ue of 7.02 classes. Results on the second cycle showed an increase in the graduat i on rate of 91.7% and an average value of 7.45 classes. On the implementation of the two cycle, mastery learning studentsand the average class has reached the indicator, so that the second cycle of this research is successful , in otherwords the study is completed in the second cycle. Based on the result s of t he study it can be concluded thatlearning through games bridging wall propagation can improve learning outcomes bridging in grade IVElementary School District Kajar Lasem Rembang Academic Year 2013. The results of this study can beapplied as one alternative learning used to improve student learning outcomes.